PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI KELAS XI IPA DI SMA DHARMA PRAJA DENPASAR - Swandari, Ni Kadek Ayu Gita; Arini, Ni Wayan; Adi Armini, Ida Ayu (UHN IGB Sugriwa Denpasar, 2023)
The problem based learning model is an innovative learning model that can provide active learning conditions for students. Problem Based Learning is a learning model that involves students to learn knowledge related to problems and at the same time has the skills to solve problems, from the experience of solving problems on their own without help from the teacher causing these students to understand more so they can create a learning environment as a social system characterized by a democratic process and a scientific process. The application of the problem-based learning learning model to teaching Hindu religion and morals in class XI IPA at Dharma Praja Denpasar High School brings a new learning atmosphere because it is very liked by students in the class because learning feels fun with solving cases related to life real. The results of this study will show how the application of the problem-based learning model in Hindu religious education and character education in class XI IPA at SMA Dharma Praja Denpasar, by going through the planning stage, the implementation stage, and the evaluation stage as well as the constraints and efforts made and the implications happen.